Selective Laser Melting Fabrication of Porous Ti6Al4V Scaffolds With Triply Periodic Minimal Surface Architectures: Structural Features, Cytocompatibility, and Osteogenesis - Lv, Jia; Jin, Wenxuan; Liu, Wenhao; Qin, Xiuyu; Feng, Yi; Bai, Junjun; Wu, Zhuangzhuang; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
The relationship between pore architecture and structure performance needs to be explored, as well as confirm the optimized porous structure. Because of the linear correlation between constant C and pore architecture, triply periodic minimal surface (TPMS) based porous structures could be a controllable model for the investigation of the optimized porous structure. In the present work, three types of TPMS porous scaffolds (S, D and G) combined with four constants (0.0, 0.2, 0.4 and 0.6) were designed, and built successfully via the selective laser melting (SLM) technology. The designed feature and mechanical property of porous scaffolds were investigated through mathematical method and compression test. And the manufactured samples were co-cultured with rMSCs for the compatibility study. The results indicated that the whole manufacturing procedure was good in controllability, repeatability, and accuracy. The linear correlation between the porosity of TPMS porous scaffolds and the constant C in equations was established. The different TPMS porous scaffolds possess the disparate feature in structure, mechanical property and cell compatibility. Comprehensive consideration of the structure features, mechanical property and biology performance, different TPMS structures should be applied in appropriate field. The results could guide the feasibility of apply the different TPMS architectures into the different part of orthopedic implants.